Experimental investigations and optimisation of process parameters in micro-EDM with multiple performance characteristics. (1st January 2011) - Natarajan, N.; Arunachalam, R.M.
This study investigates the optimisation of process parameters of micro electric discharge machining (micro-EDM) for stainless steel grade 316 (SS 316) on the machining characteristics using the Grey relational analysis (GRA) method. Experiments based on the orthogonal array (OA) of Taguchi method have been carried out. The multi-response optimisation of the process parameters viz. material removal rate (MRR), tool wear rate (TWR), Diametral OverCut (DOC) and Taper (T) has been performed. By analysing the Grey relational grade matrix, the degree of influence of each process parameter on individual quality target can be measured. The current is identified to be the most influential factor of the MRR, TWR and the T. In addition, the analysis of variance (ANOVA) is also carried out to identify the most significant factor. In depth studies have also been made to examine the influence of various process parameters through SEM micrographs of machined micro-hole.